(untitled) (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
Dividend payment is an important financial decision that reflects a company’s performance and prospects from the perspective of investors. However, companies included in the LQ45 index still experience fluctuations in dividend payment policies from year to year. This study aims to analyze the effect of leverage, firm size, profitability, and liquidity on dividend payments of companies listed in the LQ45 index on the Indonesia Stock Exchange (IDX) during the 2023–2024 period. This research employs a quantitative approach using secondary data obtained from published financial statements. The sample was selected using a purposive sampling method, resulting in 33 companies with a total of 60 observations. Data analysis was conducted using panel data regression with the assistance of SPSS software. Leverage is measured by the Debt to Asset Ratio (DAR), firm size by the natural logarithm of total assets (LnTA), profitability by Return on Assets (ROA), liquidity by the Current Ratio (CR), and dividend payment by the Dividend Payout Ratio (DPR). The results show that leverage, firm size, profitability, and liquidity simultaneously have a significant effect on dividend payments. Partially, firm size and profitability have a positive and significant effect on dividend payments, while leverage and liquidity do not have a significant effect. These findings indicate that companies with larger firm size and higher profitability tend to have a greater ability to distribute dividends to investors.